2000
DOI: 10.1021/la0006667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein Adsorption and Immunosorption Kinetics in Photoablated Polymer Microchannels

Abstract: A preliminary characterization of protein adsorption and immunosorption kinetics carried out in polymer microchannels is reported. A photoablated poly(ethylene terephthalate) (PET) surface and a PET/polyethylene sealing laminate were used for the channel microfabrication. The surface state of the PET channel substrate and PET/polyethylene lamination were analyzed by using SEM and ATR-FTIR spectroscopy techniques. Protein adsorption and immunosorption studies were carried out using staphylococcal enterotoxin B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
3
54
0
1
Order By: Relevance
“…This may be due to the fact that immunosorption kinetics may be enhanced by the forced convection during the filling of the channel. 21 Further information on the effect of the solute diffusion coefficient and of the type of flow (pressure induced and electroosmotic flows) on the coatings can also be found in the ESI{. In particular it is verified that the results of this work can be extrapolated to longer channels, provided that the residence time is respected (e.g.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…This may be due to the fact that immunosorption kinetics may be enhanced by the forced convection during the filling of the channel. 21 Further information on the effect of the solute diffusion coefficient and of the type of flow (pressure induced and electroosmotic flows) on the coatings can also be found in the ESI{. In particular it is verified that the results of this work can be extrapolated to longer channels, provided that the residence time is respected (e.g.…”
supporting
confidence: 54%
“…After this, the washing buffer (0.1% Tween-20 (SIGMA) in PBS) was pumped at the same inlet at a rate of 270 mL h 21 for 1 minute to ensure an efficient washing of the unadsorbed proteins. 21 At this point, the fluorescence of adsorbed antibody on the channel wall was measured with the confocal microscope, giving the t 0 value. The protein solution was then pumped in the same channel for an additional time t 1 , followed by washing and measurement, giving the t 0 + t 1 value, and so forth.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, heterogeneous immunoassays replace CE with a washing step and have been demonstrated on microchip platforms [34 ,35-40]. The key advantage of microfluidics in this case is to bring antibodies and antigens in such close proximity that diffusion is no longer a limiting factor: Rossier et al [41] showed that depletion of the whole microchannel volume occurred in less than 5 min. Moreover, heterogeneous immunoassays allow the concentration of captured antigen by flowing the sample solution over the antibody bed in an efficient fashion.…”
Section: Time-to-results Decreasementioning
confidence: 99%
“…The microchannel fabrication has already been described 18,33 and the confocal microscope set up follows ref. 27.…”
Section: Methodsmentioning
confidence: 99%
“…17 The studies dealing with transport and adsorption of proteins on a substrate define different regimes, depending on the adsorbatesorbent couple. A diffusional limitation of the processes is observed when the adsorption kinetics is much faster than the diffusion: 18 each protein molecule that reaches the surface is immediately adsorbed and the concentration of analyte near the wall tends to zero. On the other hand, when adsorption is much slower than diffusion controlled mass transport, kinetics plays an important role.…”
Section: Introductionmentioning
confidence: 99%